PENGARUH KUALITAS PELAYANAN TAKSI ONLINE “MY BLUEBIRD’ DAN “GRAB” TERHADAP CITRA PERUSAHAAN - Susan Sri Apriyani; Marwan Mahmudi (Jurnal Visi Komunikasi, 2020)
Bluebird   and   Grab   are   two   professional   transportation   service companies in Indonesia. The two have been competiting to serve their best to satisfy the customers so the positive image will stay remain. The concept of this research  is  using  theory  quoted  from  Kotler  of  serving  quality  and  company image  by  Shirley  Harrison.  Method  used  quantitative  approach  in possitivm  paradigma  and  comparative  study.  The  survey  method  is  using questionaire and the score of the result has been measured using Likert scale.. The questionaire has been sproud to 77 of Mercu Buana University students of Communication, major of Public Relations in 2015 to 2017 that has been a user of Bluebird Taxi and Grab Car. The data has been processed using SPSS 20 in Person’s  correlation,  simple  linear  regretion  test,  and  paired  sample  t-test. There, we found the strong connection of Taksi Bluebird service quality to the company image for 0.792 and also of the Grabcar for 0.62. It proves the impact of service quality to the company image. The difference is that the contribution of service quality to Bluebird Taxi company is 62.7% and to Grabcar company is 39.4%. It’s because Bluebird Taxi focuses more to the transportation service